Collectibility Improvement In PT. Kaltim Prima Coal Receivables Management: A Framework Roadmap Proposal - Zuhri Ruslan; Anggoro Budi Nugroho (Jurnal sosial dan sains, 2022)
Background : The Importance of efficient working capital management is indisputable given that a firm’s viability relies on the financial manager’s ability to effectively manage receivables, inventory, and payables. One of widely used measurement to calculate the effectiveness of working capital management is Cash Conversion Cycle. Purpose : Traditional Cash Conversion Cycle is calculated using items from Financial Statement. However, it is proofed to be overstated compare to the actual calculation. Based on a comparison with Cash Conversion Cycle of another company listed on Indonesian Stock Exchange, Cash Conversion Cycle of PT Kaltim Prima Coal seems to be superior with lower days it needs to convert inventory into cash and longer time to pay its payables. Method: This research uses a quantitative approach method. Results : The research found that based on the regression method, days of late payment and sales amounts of late payment have significant relationship with Profit. Days of late payment and sales amounts of late payment have significant relationship with ROA. And, Days of late payment and sales amounts of late payment also have significant relationship with NPM. Conclusion : PT. Kaltim Prima Coal are recommended to implement analysis of Risk Quadrant on periodic basis, to arrange Letter of Credit training to adopt Company Bank’s point of view in reviewing the Letter of Credit, to implement Letter of Credit checklist to reduce discrepancy rate, to arrange objective review of examining the extra staff requirement, and to develop Credit Policy.